Practical and Ethical Solutions for Remote Applied Learning Experiences in Global Health. Issue 1 (19th August 2020) - Kalbarczyk, Anna; Harrison, Meagan; Sanguineti, Maria Cecilia Dedios; Wachira, Juddy; Guzman, Carlos A. Faerron; Hansoti, Bhakti
Global health trainees rely on immersive experiences to apply their classroom knowledge in real-world settings. However, during the COVID-19 pandemic travel has come to a halt and short-term experiences are no longer available in their current form. As with didactic material, global health programs have an opportunity to innovate the delivery of applied learning, providing trainees with robust, mentored experiences that promote the acquisition of core global health competencies. We provide a series of practical solutions for remote applied learning including case-based learning, pathfinder pedagogy, virtual reality simulations, and twinning. We further describe the role of these approaches in addressing common criticisms of short-term experiences and their potential for creating new win-win dynamics between institutions and trainees.